Pengaruh Intellectual Capital, Ukuran Perusahaan, Struktur Modal, dan Likuiditas Terhadap Kinerja Keuangan Perusahaan Teknologi - Nur Shodiq; Diah Nurdiwaty; Linawati (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to analyze the effects of intellectual capital, firm size, capital structure, and liquidity ratio on the financial performance of technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period, both individually (partially) and collectively (simultaneously). Method: This study employed a quantitative approach with a causal-comparative (ex post facto) design. Secondary data were obtained from the financial statements of 17 technology companies listed on the Indonesia Stock Exchange (IDX) during 2023–2025, selected from a population of 47 companies using purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS Statistics 23. Finding: intellectual capital and firm size have a positive and significant effect on financial performance. Meanwhile, capital structure and liquidity ratio do not have a significant effect on financial performance. Simultaneously, intellectual capital, firm size, capital structure, and liquidity ratio significantly affect the financial performance of technology companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. Novelty: The novelty of this study lies in positioning intellectual capital as the primary factor influencing financial performance and focusing on technology sector companies listed on the Indonesia Stock Exchange (IDX), considering that this sector is highly dependent on knowledge, innovation, and intangible assets in creating value added. This novelty is further strengthened by the increasing number of technology issuers in recent years, reflecting the rapid growth of the technology sector and making this study more relevant to the current conditions of the Indonesian capital market.